Kajian Perbandingan Akurasi DTM Pengolahan Data Foto Udara Menggunakan Metode Otomatis Dan Semi-Otomatis Filtering - Raynier Geraldino Dadu Kerong; Martinus Edwin Tjahjadi; Fransisca Dwi Agustina (Jambura Geoscience Review, 2022)
Advances in UAV technology produce various superior products that can be utilized for the development and analysis of natural dynamics. One of them is DTM which is a visual representation of the shape of the ground surface that is displayed in 3 dimensions. DTM is obtained from the results of DSM filtering, where all features above the ground are digitally removed using a certain method. To produce a good DTM, a good quality DSM is needed, therefore a Horizontal and Vertical accuracy analysis was carried out based on ASPRS 2015. In this study, two software with different data processing methods were used, namely automatic filtering and semi-automatic filtering from DSM to DTM. To determine the quality of DTM, spot-height data is used as a comparison which is considered to be the actual form in the field. From the series of data processing processes, DTM results were obtained which were then tested for accuracy utilizing statistical validation tests using the calculation of RMSEZ values and non-statistical validation tests (Visual) using the transverse profile method. The test results show that the DTM produced by the PCI Geomatica software with the semi-automatic filtering method has more accurate and precise quality than the DTM from the SAGA GIS software with the automatic filtering method with an elevation value of 1,249 m and RMSEz 3,542 m to the spot-height. Then the visualization of the DTM transverse profile produced by the PCI Geomatica software semi-automatic filtering method to the spot height also does not appear to experience a significant difference where the elevation at Point 1 is 0.5 m and Point 2 is 0.5 m.